Evaluation of Cognitive Function When Hearing One's Own Name in Patients With Brain Injuries in Early Developmental Stages. Issue 3 (May 2017) - Tamura, Kaori; Mizuba, Takaaki; Okamoto, Tsuyoshi; Matsufuji, Mayumi; Takashima, Sachio; Iramina, Keiji
Abstract : Purpose: The level of residual cognitive function in patients with early brain injury is a key factor limiting rehabilitation and the quality of life. Although understanding residual function is necessary for appropriate rehabilitation, the extent of its effects on cognitive improvement remains unknown. This study evaluated cognitive function in patients with severe motor and intellectual disabilities after early brain injuries due to cerebral hemorrhage or periventricular leukomalacia. We focused on neural responses to hearing the subject's own name (SON). According to previous studies, differences in response to SON are associated with several types of cognitive dysfunction. Methods: We examined healthy subjects (aged 21.4 ± 1.10 years; control) and patients with a previous brain injury (aged 13–27 years at the time of our analysis) resulting in periventricular leukomalacia or a cerebral hemorrhage during the perinatal period or childhood. We recorded EEG responses to the SON and to other Japanese words, obtaining EEG-evoked potentials with wavelet transformations. Results: Compared with healthy controls, beta power (not alpha power) revealed differences in response to SON by patients with brain injury, especially those with cerebral hemorrhage. Conclusions: We suggest that alpha and beta power differences reflect different cognitive functions and that the SON response reveals more than one process. Beta powers may reflect the intellectual disability of cognitive function in response to self-relevant stimuli, especially in patients with cerebral hemorrhage. Meanwhile, alpha powers did not differ from those of the healthy controls, suggesting that the patients perhaps paid attention to their own names. Abstract : Supplemental Digital Content is Available in the Text.